2021
DOI: 10.1111/jfd.13491
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of Edwardsiella piscicida isolates from Mississippi catfish aquaculture with an assessment of virulence in channel and channel × blue hybrid catfish

Abstract: The bacterium Edwardsiella piscicida causes significant losses in global aquaculture, particularly channel (Ictalurus punctatus) × blue (I. furcatus) hybrid catfish cultured in the south-eastern United States. Emergence of E. piscicida in hybrid catfish is worrisome given current industry trends towards increased hybrid production. The project objectives were to assess intraspecific genetic variability of E. piscicida isolates recovered from diseased channel and hybrid catfish in Mississippi; and determine vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 96 publications
(185 reference statements)
3
17
0
Order By: Relevance
“…Correlating with increased hybrid production has been an increase in the number of E. piscicida diagnoses at the Aquatic Research and Diagnostic Laboratory (ARDL) at the Thad Cochran National Warmwater Aquaculture Center (NWAC) in Stoneville, MS, where hybrids make up ~50% of total diagnostic submissions to the ARDL, yet account for >90% of E. piscicida diagnoses (Griffin et al., 2019). This corroborates research data indicating increased virulence of E. piscicida in hybrid catfish (López‐Porras et al., 2021; Reichley et al., 2018). The emergence of E. piscicida in hybrid catfish is worrisome given current industry trends towards increased hybrid production.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Correlating with increased hybrid production has been an increase in the number of E. piscicida diagnoses at the Aquatic Research and Diagnostic Laboratory (ARDL) at the Thad Cochran National Warmwater Aquaculture Center (NWAC) in Stoneville, MS, where hybrids make up ~50% of total diagnostic submissions to the ARDL, yet account for >90% of E. piscicida diagnoses (Griffin et al., 2019). This corroborates research data indicating increased virulence of E. piscicida in hybrid catfish (López‐Porras et al., 2021; Reichley et al., 2018). The emergence of E. piscicida in hybrid catfish is worrisome given current industry trends towards increased hybrid production.…”
Section: Introductionsupporting
confidence: 91%
“…Using multilocus sequence analysis (MLSA) and virulence gene profiling, López‐Porras et al. (2021) identified important differences between MLSA‐groups in the presence of several virulence‐related factors. The aim of this study was to build upon this previous work and evaluate if these genetic differences affect efficacy of E .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the ESC vaccine along with its effective delivery to immunocompetent catfish fingerlings has allowed for better survival of both channel catfish and hybrid catfish fingerlings on commercial catfish farms (Kumar, Byars, et al, 2019; Kumar, Li, et al, 2019). Recent studies suggested that the ESC vaccine also offers cross protection against E. piscicida (Griffin et al, 2020; López‐Porras et al, 2021), an emerging disease in hybrid catfish (Griffin et al, 2019; Reichley et al, 2018). Since the inception of this ESC vaccination program in 2013, ~1.5 billion catfish fingerlings have been vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA finger map of V. para haemolyticus showed a high degree of genetic diversity among isolates, and REP-PCR can distinguish isolates with different virus types ( Ma et al, 2013 ). REP-PCR was used to screen 158 Edwardsiella piscicida isolates recovered from diseased channel and hybrid catfish in Mississippi to assess intraspecific genetic variability ( López-Porras et al, 2021 ). The operation of this method is relatively simple and can provide some valuable reference for isolating SSOs of aquatic products.…”
Section: The Analysis Technologies Of Ssosmentioning
confidence: 99%